2009
DOI: 10.1128/cvi.00160-09
|View full text |Cite
|
Sign up to set email alerts
|

Glycoprotein 96-Mediated Presentation of Human Immunodeficiency Virus Type 1 (HIV-1)-Specific Human Leukocyte Antigen Class I-Restricted Peptide and Humoral Immune Responses to HIV-1 p24

Abstract: The heat shock protein (HSP) gp96 is a 96-kDa glycoprotein of the endoplasmic reticulum that is believed to be involved in antigen processing as an intermediate carrier of peptides. The mechanism of immunogenicity of gp96-peptide complexes involves the interaction of the gp96 with macrophages or dendritic cells through the receptor CD91 (5), followed by representation of the gp96-chaperoned peptides by the major histocompatibility complex class I (MHC class I) and MHC class II molecules of the macrophage or de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 28 publications
(39 reference statements)
0
7
0
1
Order By: Relevance
“…It is well documented that gp96, when reconstituted in vitro with tumor associated antigens such as HER-2 (Pakravan et al, 2010), or antigens from virus, such as HPV or HIV (SenGupta et al, 2004;Li et al, 2005;Gong et al, 2009), elicits potent CD8 + and CD4 + T-cell responses against tumor and virus. In agreement with these studies, our recent work showed that gp96 as an adjuvant has the ability to induce HBV specific CTL responses.…”
Section: Introductionmentioning
confidence: 98%
“…It is well documented that gp96, when reconstituted in vitro with tumor associated antigens such as HER-2 (Pakravan et al, 2010), or antigens from virus, such as HPV or HIV (SenGupta et al, 2004;Li et al, 2005;Gong et al, 2009), elicits potent CD8 + and CD4 + T-cell responses against tumor and virus. In agreement with these studies, our recent work showed that gp96 as an adjuvant has the ability to induce HBV specific CTL responses.…”
Section: Introductionmentioning
confidence: 98%
“…In parallel experiment, immunization of wild BALB/c mice with p24-gp96 or p24-N336 mixture or with recombinant p24-N336 fusion protein elicited p24-specific antibody responses [48].…”
Section: G Modelmentioning
confidence: 99%
“…The MHC-I presentation was executed by cytosolar, endoplasmic reticulum-dependent pathway [47]. In another study, gp96 from human liver or its Nterminal recombinant fragment (N336, amino acids 22-336) were used as adjuvants for p24 protein or its HLA-A2-restricted peptide (FLQSRPEPTA) [48]. Immunization of HLA-A2 transgenic mice with FLQSRPEPTA-gp96 mixture induced peptide-specific cytotoxic-Tlymphocyte responses confirmed by ELISPOT and MHC-I tetramers.…”
Section: G Modelmentioning
confidence: 99%
“…Epitopes are short peptides, and their immunogenicity is low unless introduced into a carrier protein (39). Here we used p24, an immunodominant protein of HIV-1 widely used in the development of HIV vaccines (15), as the protein backbone for incorporation of M. tuberculosis epitopes. The gene segments of these epitopes were grafted into various regions of the p24 gene scaffold, and a multiepitope DNA vaccine containing immunogens from M. tuberculosis and HIV-1 was obtained.…”
mentioning
confidence: 99%